Liquid Metal Microscale Deposition enabled High Resolution and Density Epidermal Microheater for Localized Ectopic Expression in Drosophila. Issue 3 (5th October 2021) - Wang, Bei; Gao, Junjun; Jiang, Jiajun; Hu, Zenghui; Hjort, Klas; Guo, Zheng; Wu, Zhigang
Abstract: Localized ectopic expression of enteroendocrine cells in fruit flies provides a convenient model for studying human intestinal diseases, e.g., inflammatory bowel disease, that need urgent attention. Due to its noninvasive feature, thermal activating ectopic expression is an excellent option, but it demands local heating of the tiny and delicate live flies' abdomen (≈1 × 1 mm 2 ) without blocking their breath, instead of global heating of the whole body. This work proposes a thin, high‐resolution, and density liquid metal (LM) microheater with gas permeability and sufficient compliance to provide homogenous local heating to the fly's tiny abdomen. A depositing technique is developed that can make microscale thin (5 µm), smooth ( S a  = 0.8 µm), gas permeable LM film for such microheater by introducing LM micrometer/sub‐micrometer particles. Collision induced LM particle merging and hence sintering is proposed to solve low conductivity due to their particular shells of micrometer/sub‐micrometer particles. The deposition can conformally print on the wavy or rough surface due to the fine particle size. With a shadow mask, this microscale deposition can enable high yield and reproducible thin LM patterning with high resolution, density, and precision simultaneously. Furthermore, it is demonstrated that epidermal patches can compliantly attach onto the wrinkle skin and fingerprint. Finally, by applying such a microheater on the fly abdomen, localized ectopic expression of enteroendocrine cells is successfully demonstrated. Abstract : A thin microheater is proposed that can compliantly attach to the fruit fly abdomen for thermally activating local ectopic expression enteroendocrine cells in tiny and delicate Drosophila targeting for human disease models. This heater is enabled by a microscale depositing technique of liquid metal (LM), which can deposit thin, smooth, and gas permeable film by merging original insulated micrometer/sub‐micrometer LM particles.